ROLE OF OTOSTRNGTH PLUS IN SENSORINEURAL HEARING LOSS, VERTIGO AND TINNITUS - Dr Harsimrat Singh; Dr. Harpreet Khullar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Sensorineural hearing loss, vertigo and tinnitus is one of the most frequently encountered problem in day-to-day practise. Despite best medical management, these patients often remain dissatisfied with improvement and search for more treatment strategies continues. Among the used medicinal plants, Ginkgo biloba and magnesium oxide is frequently used in the treatment. Aims and objectives: To study the efficacy of Otostrngth plus (Ginkgo Biloba+Methylcobalamin+ Magnesium oxide) in cases of sensorineural hearing loss along with regard to improvement in hearing, vertigo and tinnitus. Material and Methods: 200 patients with sensorineural hearing loss were included and randomly allocated into any of 2 groups being studied. Group- A received Otostrngth plus and Group – B received conventional regimen (oral vitamin A and vitamin B complex). Results: There were subjective improvement in hearing in 80 patients in Group A compared to 60 in Group B. 64 patients in Group A compared to 44 patients in Group B showed subjective improvement in tinnitus. 26 patients in Group A showed greater than 10 db improvement in hearing compared to only 14 patients in Group B. Conclusion: Otostrngth plus together with conventional therapy helps in better patient management and improved symptomatology.